2007
DOI: 10.1002/art.22873
|View full text |Cite
|
Sign up to set email alerts
|

Role of raloxifene as a potent inhibitor of experimental postmenopausal polyarthritis and osteoporosis

Abstract: Objective. In postmenopausal rheumatoid arthritis (RA), both estrogen deficiency and the inflammatory disease contribute to the development of generalized osteoporosis. Hormone replacement therapy (HRT) with estradiol preserves bone mineral density (BMD) and ameliorates arthritis, but long-term therapy is no longer an option due to significant side effects. We therefore used a mouse model of human RA to test the hypothesis that a selective estrogen receptor modulator (SERM), the raloxifene analog LY117018, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
7
32
1
Order By: Relevance
“…It has repeatedly been shown that treatment with E2 improves disease development in experimental models of arthritis (Jansson and Holmdahl, 1989;Nandakumar et al, 2003;Engdahl et al, 2014) shown that the second generation SERM ral inhibits experimental postmenopausal arthritis (Jochems et al, 2007). Interestingly, preliminary data from our lab show that also las and bza have beneficial effects on disease development and associated bone loss in postmenopausal collagen-induced arthritis (Andersson et al, submitted).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has repeatedly been shown that treatment with E2 improves disease development in experimental models of arthritis (Jansson and Holmdahl, 1989;Nandakumar et al, 2003;Engdahl et al, 2014) shown that the second generation SERM ral inhibits experimental postmenopausal arthritis (Jochems et al, 2007). Interestingly, preliminary data from our lab show that also las and bza have beneficial effects on disease development and associated bone loss in postmenopausal collagen-induced arthritis (Andersson et al, submitted).…”
Section: Introductionmentioning
confidence: 82%
“…Conversely, hormone replacement therapy including E2 ameliorates rheumatoid arthritis and multiple sclerosis (D'Elia et al, 2003;El-Etr et al, 2011) and treatment with E2 inhibits experimental models of arthritis and multiple sclerosis (Jansson and Holmdahl, 1989;Nandakumar et al, 2003;Engdahl et al, 2014). Our group has previously demonstrated that ral ameliorates arthritis and protects against bone loss in experimental collagen-induced arthritis (CIA) (Jochems et al, 2007). Interestingly, preliminary data show that also las and bza Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, an epidemiological study showed that HRT users had decreased risk of developing seropositive RA (in this case having antibodies against citrullinated peptides)-compared with nonusers (10). Estradiol is undoubtedly protective in mice with experimental arthritis (11,12). We have previously demonstrated that the SERMs, raloxifene, lasofoxifene, and BZA, inhibit joint inflammation and protect from bone loss in experimental arthritis (11,12).…”
mentioning
confidence: 99%
“…Treatment with aromatase inhibitor has decreased trabecular bone mass but has minimal effect on cortical bone area in intact male rats [30,51]. Selective estradiol receptor modulators (SERMs) increase cortical and trabecular bone mass in orchiectomized rats and increases trabecular bone mass in intact males [52,53]. DHEA and androstenedione increase trabecular bone formation in ovariectomized rats.…”
Section: ) Epidemiology Of Osteopenia and Osteoporosismentioning
confidence: 99%